Providing fault tolerance in wireless access networks. - Tipper, D. (IEEE Communications magazine)
Research and development on network survivability has largely focused on public switched telecommunications networks and high-speed data networks with little attention on the survivability of wireless access networks supporting cellular and PCS communications. This article discusses the effects of failures and survivability issues in PCS networks with emphasis on the unique difficulties presented by user mobility and the wireless channel environment. A simulation model to study a variety of failure scenarios on a PCS network is described, and the results show that user mobility significantly worsens network performance after failures, as disconnected users move among adjacent cells and attempt to reconnect to the network. Thus, survivability strategies must be designed to contend with spatial as well as temporal network behavior. A multilayer framework for the study of PCS network survivability is presented. Metrics for quantifying network survivability are identified at each layer. Possible survivability strategies and restoration techniques for each layer in the framework are also discussed